Arthroscopic treatment of symptomatic calcific periarthritis on the medial side of the knee after posterior cruciate ligament reconstruction: Case report and literature review - Eui-Chan Jang; Han-Jun Lee; Seong Hwan Kim; Yoon-Ho Kwak (Acta Orthopaedica et Traumatologica Turcica)
Calcific periarthritis in the distal femur is a rare condition. Forty two year old Asian male visited to the outpatient clinic of orthopedic department with acute excruciating knee pain. The arthroscopic posterior cruciate ligament (PCL) reconstruction was performed 20 years ago with the bonepatellar tendon-bone (BPTB) autograft combined with Trevira (polyethylene terephthalate) artificial ligament. Severe tenderness was noted incidentally over the medial epicondyle area of the distal femur which the cancellous screw was inserted for PCL reconstruction, without any preceding trauma history or medial joint line tenderness due to degenerative change. The poorly defined calcific deposition was found in plain radiograph. The arthroscopic debridement of the calcification and screw removal from the distal femur was performed due to resist to conservative treatment with analgesics. After operation, the symptoms were resolved completely. The arthroscopic debridement of calcific periarthritis should be considered in specific cases, such as refractory cases with conservative management during 4–6 weeks. We present the arthroscopic treatment of the symptomatic calcific periarthritis on distal femur after PCL reconstruction can be effective. Keywords: Calcific periarthritis, Distal femur, Arthroscopy, Posterior cruciate ligament reconstruction